Aldara‐induced dermatitis is associated with development of liver fibrosis in mice. (19th July 2018) - Maybury, C.M.; Di Meglio, P.; Smith, C.H.
Abstract : Linked Article:  Vasseur et al. Br J Dermatol 2018;179 :101–109 .